Taxes and Capital Formation. - Feldstein, Martin (National Bureau of Economic Research project report., 1987)
Economists have long recognized the importance of capital accumulation for productivity and economic growth. The National Bureau of Economic Research is currently engaged in a study of the relationship between such accumulation and taxation policies, with particular focus on saving, risk-taking, and corporate investment in the United States and abroad. The papers presented in Taxes and Capital Formation are accessible, nontechnical summaries of fourteen individual research projects within that study. Complete technical reports on this research are published in a separate volume, The Effects of.